Is There a Link Between Monetary Policy and Risk Perception in Eastern European Countries Implementing Inflation Targeting Regime? - Kansu, Aydan; Yıldırım, Nurtaç; Ozcelebi, Oguzhan (International Journal of Economics and Financial Issues, 2013)
Following the recent financial crisis of August 2007 in US, economists and policy makers hold the view that monetary policy may have an effect on real economic activity through ‘risk taking channel’ which indicates the risk behavior of economic agents and the linkages between monetary policy and perception of risk. In this study, we examine whether changes in monetary policy stance influence the risk perceptions and generates any impact on the real side of the economy in Czech Republic, Poland, Russian Federation and Turkey implementing inflation targeting. In the context of a SVAR model, we find that monetary policy does not affect risk perception reflected by stock price variability and any attempt by central banks to stimulate real economic activity through monetary policy also appears to be ineffective in these countries. Keywords: Monetary policy; Interest Rates; Stock Markets; Real Economic Activity; Risk perception; SVAR model JEL Classifications: E30; E32; E37; E43; E44; G10